PEMANFAATAN ARANG SEKAM PADI SEBAGAI ADSORBEN FENOL - Azizah Mizan; Setiawan .; Pratiwi . (Poltekkes Kemenkes Surabaya, 2016)
Phenolic compounds is water pollutants because toxic at certain levels. One methods degrade phenol is adsorption. By the high of husk waste, rice production mill especially in Leran Kulon, District of Tuban, can be used as absorbent to decreasing in phenol was conducted.This study used pre-experimental design with One Group Pre-Post Test Design. The research object was phenol concentration 3ppm with 14 treatment variations. Phenol concentrations was measured after direct contact with the husk charcoal provided in dose of 10 g /l and 25 g/l at minute 30, 60, and 90. The results showed the adsorption husk charcoal with dose of 25 g/l was greater than 10 g/l and the best time was 90 minutes at dose of 25 g /l with an average decrease of 63.33%.It is suggested to carry out socialization to the public on the use of rice husk as phenol adsorbent primarily to society of Leran Kulon. In addition, further research needs to carried out with addition contact time variation, dose husk choarcal, testing toward pH and temperature effect on adsorption capacity as well as testing toward ash content, water content and volatile content of the husk choarcal made